Complete mitochondrial genome of Schizopygopsis chengi chengi (Cyprinidae, Schizothoracinae, Schizopygopsis). (2nd September 2016) - Du, Zongjun; Wu, Jiayun; Lin, Rongnan; Zhu, Guangxiang; Xie, Meng; Wang, Qin; Jiang, Yanzhi; Wen, Anxiang
Abstract: The complete mitochondrial DNA sequence of Schizopygopsis chengi chengi collected from the Dadu River was determined in this study. The complete mitochondrial genome of S. chengi chengi was a circular molecule of 16 688 bp in size, and all genes showed the typical gene arrangement conforming to the vertebrate consensus. Twelve protein-coding genes (except ND6) of S. chengi chengi and other 22 Schizothoracinae species from two genera were used for phylogenetic analysis by Bayesian inference and maximum likelihood methods. The topology confirmed the close genetic relationship between S. chengi chengi and S. chengi baoxinggensis .